2009
DOI: 10.5194/acpd-9-6889-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hygroscopic growth of urban aerosol particles in Beijing (China) during wintertime: a comparison of three experimental methods

Abstract: Abstract. This paper presents hygroscopicity measurements of aerosol particles in the urban atmosphere of Beijing carried out in January 2005. Therefore, three different methods were used: 1) Combining Humidifying Differential Mobility Particle Sizer (H-DMPS) and Twin Differential Mobility Particle Sizer (TDMPS) measurements; 2) Hygroscopicity Tandem Differential Mobility Analyzer (H-TDMA) technique; 3) Calculating hygroscopic growth factors on the basis of a solubility model quantified by Micro Orifice Unifor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…The average RH during the dust events was mostly lower than 30%. Particle hygroscopic growth factor at RH = 40% in Beijing did not exceed 1.01 in January 2005 and the particles did not show obvious growth below RH 60% (Meier, et al, 2009). Therefore, the hygroscopic growth of the particles was not considered in the Mie calculations.…”
Section: Calculation Of Aerosol Extinction and Visibilitymentioning
confidence: 99%
“…The average RH during the dust events was mostly lower than 30%. Particle hygroscopic growth factor at RH = 40% in Beijing did not exceed 1.01 in January 2005 and the particles did not show obvious growth below RH 60% (Meier, et al, 2009). Therefore, the hygroscopic growth of the particles was not considered in the Mie calculations.…”
Section: Calculation Of Aerosol Extinction and Visibilitymentioning
confidence: 99%
“…In Guangzhou and Shanghai, optical methods (using nephelometers, transmissometer and photometer) were employed for the determination of hygroscopic growth factor and evaluation of scattering and light extinction of ambient aerosol (Liu et al, 2008;Jung et al, 2009;Cheng et al, 2014). While in the North China Plain a series of interrelated studies (Achtert et al, 2009;Massling et al, 2009;Meier et al, 2009;Bian et al, 2014;Liu et al, 2014) evaluated the chemical and physical influence on hygroscopic growth of atmospheric sub-micrometer particles using HTDMA, Twin Differential Mobility Particle Sizer (TDMPS), and Humidifying Differential Mobility Particle Sizer (HDMPS) for rural and urban areas. So far, direct measurement of aerosol water content at ambient conditions using a DAASS system has not been performed in China.…”
Section: Introductionmentioning
confidence: 99%
“…Massling et al [7] and Meier et al [8]reported the particle hygroscopicity in the urban atmosphere of Beijing, indicating that the hygroscopicity varied with particle size, level of pollution and season. In contrast to the dry weather in inland and Northern China, high humidity is ubiquitous in Southern China, where the hygroscopicity of aerosols is of great value to understand humidity-sensitive phenomena such as haze and fog.…”
Section: Introductionmentioning
confidence: 98%
“…In China, only a few studies have been performed with regards to the hygroscopicity of ambient aerosols [7][8][9][10]. Massling et al [7] and Meier et al [8]reported the particle hygroscopicity in the urban atmosphere of Beijing, indicating that the hygroscopicity varied with particle size, level of pollution and season.…”
Section: Introductionmentioning
confidence: 98%